Method for preparing high-strength nano-structure high-entropy alloy wire

Through vacuum smelting, hot forging and multi-pass cold-drawing deformation of the Alx(CoCrFeNi) 100-x high-entropy alloy system, a structure of nanocrystal embedded nanocrystal regions and a long fiber crystal region wrapped in high-density dislocations was prepared, which solved the problems of improving the strength of FCC high-entropy alloys and the stability of nanostructures, and achieved high-strength and good ductility of high-entropy alloy wires.

CN120366681APending Publication Date: 2025-07-25WUXI BLUE GREEN METAL MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510594407.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the strength of FCC high-entropy alloys through cold drawing deformation without introducing a second phase or external reinforcement mechanism, and maintain the stability of the nanostructure under high strain, resulting in uncontrollable material performance and difficult to meet the needs of high-end engineering fields.

Method used

Alx(CoCrFeNi) 100-x high-entropy alloy system is used to form a uniform rod material through vacuum smelting, hot forging and recrystallization annealing, and then undergo multiple passes of cold-pull deformation at room temperature or low temperature. Al element controls stacking faults to promote the formation and evolution of deformation twins, stimulate the coordinated evolution of early twins and high-density dislocations, and prepare the nanocrystal region embedded in nanotwins and the long fiber crystal region wrapped in high-density dislocations.

Benefits of technology

The high-strength nanostructured high-entropy alloy wire has been prepared, the yield strength is increased to 1631MPa, the grain size is stable in the range of 30-35nm, and it has good ductility and highly controllable tensile properties, which are suitable for mass industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120366681A_ABST
    Figure CN120366681A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a high-strength nano-structure high-entropy alloy wire, an adopted high-entropy alloy system is Alx (CoCrFeNi) 100-x (x = 0.1-2.5 at.%), a bar with a uniform structure is obtained through vacuum melting, hot forging and recrystallization annealing, then multi-pass cold drawing deformation is carried out at normal temperature or low temperature, and the high-strength nano-structure high-entropy alloy wire is obtained. The nano-structure high-entropy alloy wire with ultrahigh strength and good ductility is prepared, and after cold drawing, the wire shows a unique double-phase microstructure composed of a nano crystal region embedded by nano twin crystals and a long fiber crystal region wrapped by high-density dislocation; under the condition that a second phase is not introduced or an additional strengthening mechanism is not introduced, SFE is regulated and controlled through the Al element, formation and evolution of deformation twin crystals are promoted, co-evolution of early twin crystals and high-density dislocation is stimulated through low-temperature cold drawing, the strengthening effect is enhanced, the tensile property shows high controllability and repeatability, and the method is suitable for batch industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-entropy alloy materials, and particularly to a method for preparing high-strength nanostructured high-entropy alloy wires. Background Art

[0002] As a new type of alloy material composed of multiple main elements, high-entropy alloys (HEAs) have become a research hotspot in the field of materials science in recent years due to their unique solid solution effect and excellent mechanical properties. The face-centered cubic (FCC) structure high-entropy alloy based on CoCrFeNi shows potential in extreme environment applications due to its good low-temperature toughness and high structural stability. However, the strength of traditional FCC high-entropy alloys is generally low, and the tensile strength is usually less than 1000 MPa, making it difficult to meet the requirements of high-end engineering fields. To improve the strength, existing technologies mainly use methods such as introducing second-phase strengthening (such as precipitation phases or intermetallic compounds) or severe plastic deformation (such as high-pressure torsion, equal-channel angular pressing). However, the introduction of the second phase easily leads to a decrease in the ductility of the material, while the complex plastic deformation process has high costs, low efficiency, and is difficult to achieve large-scale production.

[0003] Cold drawing deformation, as a low-cost and high-efficiency processing method, can improve the strength of materials through dislocation accumulation and twin induction. However, traditional FCC high-entropy alloys are prone to the phenomenon of saturated microstructure evolution under high strain, limited grain refinement, and a significant decrease in strengthening efficiency. For example, the cold-drawn CoCrFeMnNi alloy reported in the existing literature shows a stable grain size when the strain ε = 4.0, and further deformation cannot effectively improve the strength. In addition, although the low-temperature cold drawing process can suppress dynamic recovery, the systematic research on the regulation of microstructure stability and strengthening mechanism is still lacking, resulting in uncontrollable material properties. Therefore, how to maintain the nanostructure stability during cold drawing, break through the strength limit of traditional FCC alloys, and achieve large-scale application of the process has become an urgent technical problem in this field.

[0004] Based on this, the present application proposes a method for preparing high-strength nanostructured high-entropy alloy wires. Summary of the Invention

[0005] The object of the present invention is to provide a method for preparing high-strength nanostructured high-entropy alloy wires to solve the problems existing in the above-mentioned prior art.

[0006] To achieve the above object, the present invention provides the following solution:

[0007] The present invention provides a method for preparing high-strength nanostructured high-entropy alloy wires, comprising the following steps:

[0008] S1. Construct a high-entropy alloy system as the initial alloy, and the composition system in the high-entropy alloy system is designed as Alx(CoCrFeNi)100-x by atomic ratio, where x is 0.1-2.5 at.%;

[0009] S2. Prepare an ingot by vacuum melting the initial alloy, and perform water quenching after homogenization treatment;

[0010] S3. Perform hot forging and machining on the ingot to obtain a rod with a diameter of 5.5 mm;

[0011] S4. Anneal the rod and then perform water quenching to form a single-phase face-centered cubic structure;

[0012] S5. Perform multi-pass cold drawing deformation on the annealed rod at room temperature or low temperature to obtain a high-strength nanostructured high-entropy alloy wire.

[0013] Preferably, in step S1, the stacking fault energy is regulated by the addition amount of Al element to promote the formation and evolution of deformation twins and inhibit grain coarsening.

[0014] Preferably, in step S1, one or more of Ti, Mo, V, Cu, Mn, Zr, Nb, Si, and B are further included in the high-entropy alloy system.

[0015] Preferably, in step S2, the temperature of the vacuum melting is 1873-1973 K and the time is 1-2 h.

[0016] Preferably, in step S2, the temperature of the homogenization treatment is 1450-1500 K and the time is 5-8 h.

[0017] Preferably, in step S3, the temperature of the hot forging is 1300-1350 K.

[0018] Preferably, in step S4, the temperature of the annealing is 1150-1200 K and the time is 1-2 h.

[0019] Preferably, in step S5, the temperature of the low-temperature environment is 77 K, and the low-temperature environment is a liquid nitrogen environment, which is used to stimulate the cooperative evolution of deformation twins and high-density dislocations and accelerate tissue refinement.

[0020] Preferably, in step S5, the cold drawing is performed to a strain of 8.0 at room temperature and to a strain of 2.0 at low temperature.

[0021] Preferably, in step S5, the average grain size of the high-strength nanostructured high-entropy alloy wire is 33±5 nm, the twin thickness is 3-4 nm, and the dislocation density is (2.0±0.2)×10 15 m -2 .

[0022] The present invention has achieved the following beneficial technical effects compared with the prior art:

[0023] A method for preparing a high-strength nanostructured high-entropy alloy wire provided by the present invention uses a high-entropy alloy system of Alx(CoCrFeNi)100-x (x = 0.1 - 2.5 at.%). By vacuum melting, hot forging, and recrystallization annealing, a bar with uniform structure is obtained. Subsequently, multi-pass cold drawing deformation is carried out at normal or low temperature to prepare a nanostructured high-entropy alloy wire with both ultra-high strength and good ductility. After cold drawing, the wire exhibits a unique dual-phase microstructure composed of a nanocrystalline region embedded with nanoscale twins and a long fibrous crystal region wrapped by high-density dislocations; without introducing a second phase or external strengthening mechanism, the present application regulates the stacking fault energy (SFE) through Al element, promotes the formation and evolution of deformation twins, and low-temperature cold drawing stimulates the synergistic evolution of early twins and high-density dislocations, enhancing the strengthening effect. The tensile properties show high controllability and repeatability, and are suitable for batch industrial production.

[0024] The present application has the following advantages:

[0025] 1. Ultimate strength breakthrough: The yield strength of the Alx(CoCrFeNi)100-x system high-entropy alloy wire prepared by this method is increased to 1631 MPa when drawn to ε = 2.0 at 77 K, and further increased to 2300 MPa when drawn to ε = 8.0 at room temperature, which is one of the materials with the highest strength among the currently known FCC HEAs of the same kind;

[0026] 2. Excellent tissue stability: The twin-dislocation synergistic mechanism induced during cold drawing enables the material to maintain the grain size stable in the range of 30 - 35 nm under high strain conditions, avoiding tissue softening and ensuring long-term service reliability;

[0027] 3. Clear and controllable strengthening mechanism: By systematically analyzing the dislocation density, twin thickness, and boundary strengthening effect, and clarifying the contribution ratio of Hall-Petch strengthening and Taylor strengthening during cold drawing, it is beneficial to establish a material design and performance prediction model;

[0028] 4. Flexible composition design space: The Al content has a wide regulation range (0.1 - 2.5 at.%), is applicable to various working conditions and performance requirements, and has good expandability of the alloy system;

[0029] 5. Strong green manufacturing and industrial feasibility: It does not rely on rare precious metals or complex heat treatment processes, has a clear process flow, strong equipment versatility, and is suitable for large-scale industrial promotion;

[0030] 6. Strong adaptability to multiple scenarios: Due to its super strength, good ductility and tissue stability, this wire can be widely used in fields such as aerospace, high-speed rail, nuclear energy, cryogenic containers, electromagnetic shielding and precision transmission, etc., and has good market prospects and technical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0032] Figure 1 It is the initial microstructure diagram of Embodiment 1 of the present invention;

[0033] Figure 2 It is the mechanical property test diagram of Embodiment 1 of the present invention;

[0034] Figure 3 It is the EBSD characterization diagram of Embodiment 1 of the present invention;

[0035] Figure 4 It is the STEM-BF micrograph of Embodiment 1 of the present invention;

[0036] Figure 5 It is the synchrotron x-ray diffraction diagram of Embodiment 1 of the present invention;

[0037] Figure 6 It is the tissue characteristic diagram of Embodiment 2 of the present invention;

[0038] Figure 7 It is the mechanical property test diagram and microstructural diagram of Embodiment 2 of the present invention;

[0039] Figure 8 It is the BF-STEM micrograph of Embodiment 2 of the present invention;

[0040] Figure 9 It is the TEM diagram of Embodiment 2 of the present invention;

[0041] Figure 10 It is the high-energy x-ray diffraction diagram of Embodiment 2 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0042] The following will clearly and completely describe the technical solutions in the embodiments of the present invention with reference to the drawings in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.

[0043] The object of the present invention is to provide a method for preparing a high-strength nanostructured high-entropy alloy wire rod to solve the problems existing in the prior art.

[0044] The method of the present invention comprises the following steps:

[0045] S1. Construct a high-entropy alloy system as the initial alloy. In the high-entropy alloy system, the composition system is designed according to the atomic ratio as Alx(CoCrFeNi)100-x, where x is 0.1-2.5 at.%; the stacking fault energy is regulated by the addition amount of Al element to promote the formation and evolution of deformation twins and inhibit grain coarsening; the regulation range of Al content is wide, which is applicable to various working conditions and performance requirements and has good alloy system expandability; of course, in order to further improve the performance of the high-entropy alloy, elements such as Ti, Mo, V, Cu, Mn, Zr, Nb, Si, B, etc. can also be added to the system; among them,

[0046] The role of Ti is to improve the strength and high-temperature stability of the alloy and promote solid solution strengthening; it may form nano-precipitates (such as Laves phase) to enhance the creep resistance, which is suitable for scenarios such as high-temperature structural materials and aerospace components;

[0047] The role of Mo is to significantly improve the corrosion resistance (especially in acidic or chlorine-containing environments), enhance the high-temperature strength and creep resistance; it promotes the stability of the body-centered cubic (BCC) structure, and the suitable application scenarios include chemical equipment, marine environment materials, etc.;

[0048] The role of V is to refine grains, improve strength and toughness; it synergistically enhances the corrosion resistance with Cr, and the suitable application scenarios include high-strength structural parts, wear-resistant coatings, etc.;

[0049] The role of Cu is to regulate the phase structure (such as inducing the face-centered cubic FCC phase) and improve the ductility; however, excessive amount may lead to a decrease in corrosion resistance; therefore, its application scenario is for components that require plastic deformation ability;

[0050] The role of Mn is to stabilize the FCC phase, improve plasticity and fatigue resistance; it may reduce the strength and can be used in low-temperature or high-impact environments;

[0051] The role of Zr is to refine grains, improve oxidation resistance and high-temperature strength, and can form a strengthening phase with Al. The application scenarios include high-temperature oxidation coatings, nuclear industry materials, etc.;

[0052] The role of Nb is to form stable carbides or Laves phase, enhance hardness and wear resistance, and inhibit intergranular corrosion; its application scenarios are mostly wear-resistant tools and nuclear reactor materials;

[0053] The role of Si is to improve the casting fluidity, increase hardness and wear resistance, but excessive amounts may lead to brittleness. Application scenarios include casting alloys, wear-resistant coatings, etc.;

[0054] The role of B is to refine grains, strengthen grain boundaries, form hard boride phases, and increase hardness. Application scenarios are superhard coatings and wear-resistant materials;

[0055] S2. Vacuum melt the initial alloy at a temperature of 1873 - 1973K for 1 - 2h to prepare an ingot, and then homogenize it at a temperature of 1450 - 1500K for 5 - 8h and water quench;

[0056] S3. Hot forge and machine the ingot at a temperature of 1300 - 1350K to obtain a rod with a diameter of 5.5mm;

[0057] S4. Anneal the rod and then water quench. The annealing temperature is 1150 - 1200K and the time is 1 - 2h to form a single-phase face-centered cubic structure;

[0058] S5. Perform multi-pass cold drawing deformation on the annealed rod at room temperature or low temperature. When at room temperature (298K), cold draw it to a strain of 8.0. When at low temperature (77K, in a liquid nitrogen environment), cold draw it to a strain of 2.0, which is used to stimulate the synergistic evolution of deformation twins and high-density dislocations, accelerate grain refinement, and obtain a high-strength nanostructured high-entropy alloy wire composed of a nanocrystalline region embedded with nanotwins and a long-fiber crystal region wrapped by high-density dislocations. The average grain size of the high-strength nanostructured high-entropy alloy wire is 33 ± 5nm, the twin thickness is 3 - 4nm, and the dislocation density is (2.0 ± 0.2)×10 15 m -2 。

[0059] To make the above objects, features, and advantages of the present invention more obvious and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0060] Example 1:

[0061] This embodiment provides a method for preparing a high-strength nanostructured high-entropy alloy wire of an Al0.1CoCrFeNi high-entropy alloy system. High-purity (≥99.95%) Al, Co, Cr, Fe, and Ni are selected and melted in a molar ratio to form an Al0.1CoCrFeNi alloy. Homogenization heat treatment is carried out at 1473 K for 8 hours. After water quenching, it is hot forged into a bar and machined to a diameter of 5.5 mm. Subsequently, it is annealed at 1173 K for 1 hour to obtain a fully recrystallized FCC single-phase structure. The sample is subjected to multi-pass cold drawing at room temperature (298 K) and liquid nitrogen temperature (77 K) respectively, and finally drawn to a diameter of 2.0 mm (strain ε = 2.0). Tests show that the yield strength of the 77 K cold-drawn sample reaches 1631 MPa, and there are a large number of nanotwins and refined grains in the microstructure, and the grain size is about 85 nm.

[0062] The applicant detected the above materials, and the detection results are as Figure 1-4 shown. Figure 1 This is the initial microstructure of the high-entropy alloy in this embodiment. Among them, (a) is the EBSD phase of the Al0.1CoCrFeNi HEA sample after annealing at 1173 K for 1 h, (b) is the inverse pole figure showing the single-phase fcc structure with complete grain recrystallization, (c) is the corresponding statistical grain size distribution, (d) is the synchrotron x-ray diffraction pattern of the annealed HEA, the attached figure is the corresponding synchrotron diffraction ring, (e) is the bright-field TEM image showing the fully recrystallized triple grain boundary and dislocation morphology, (f) is the selected area electron diffraction pattern (SAED) obtained from the

[110] FCC zone axis, and (g) is the TEM-EDS map showing the uniform element distribution in Al0.1CoCrFeNi HEA, corresponding to Figure (e).

[0063] Figure 2 This is the room-temperature mechanical properties of aqueous and cryogenic Al0.1CoCrFeNi HEAs. (a) is the tensile engineering stress-strain curves at different tensile strains (ε = 0, 1.0, 2.0), and the attached figure is the detailed engineering stress-strain curve; (b) shows the changes of the ultimate tensile strength (UTS) and yield strength (YS) with the tensile strain respectively.

[0064] Figure 3 This is the macroscopic EBSD characterization of 298 K and 77 K drawn wires at 0.2 - 2.0 strain. (a, c) are the IPF maps of the aqueous drawing (298 K) and (c, d) the cryogenic drawing (77 K) of Al0.1CoCrFeNi HEA wires and (b, d) the corresponding BC (band contrast) maps.

[0065] Figure 4The representative STEM-BF micrograph shows the microstructure evolution of 1173K / 1h annealed Al0.1CoCrFeNi under 298K tensile strain. The low-magnification BF micrograph is on the left, the high-magnification image is in the middle, and the corresponding SAED pattern is obtained from the area circled by the yellow dashed line, (a1a3)=0.2; (b1b3)=0.6; (c1-c3)=1.0; (d1-d3)=2.0.

[0066] Figure 5 Synchrotron X-ray diffraction patterns of 1173K / 1h annealed Al0.1CoCrFeNi HEA wires at different tensile strains at 298K (a) and 77K (b).

[0067] Example 2:

[0068] This example provides a method for high-strength nanostructured high-entropy alloy wires of the Al2.5Ti2.5(CoCrFeNi)95 high-entropy alloy system. The Al2.5Ti2.5(CoCrFeNi)95 alloy is obtained by melting high-purity metal raw materials of Al, Ti, Co, Cr, Fe, and Ni. The ingot is annealed at 1373K for 60 minutes and water quenched to obtain a uniform FCC-structured bar with a grain size of about 78μm. Subsequently, multi-pass cold drawing is carried out at room temperature until the final diameter is 0.056mm, corresponding to a strain of ε = 8.0. TEM characterization shows that a duplex structure of nanocrystalline regions (NGR) and long fiber grains (LFG) is formed in the wire, with an average grain size of about 33nm and a dislocation density as high as 2×10 15 m -2 , and the tensile strength reaches 2300MPa.

[0069] The applicant detected the above materials, and the detection results are as Figures 6-10 shown, Figure 6 are the tissue characteristics of Al2.5Ti2.5(CoCrFeNi)95 HEA after annealing. (a) The X-ray diffraction pattern shows a single-phase FCC crystal structure; (b) the EBSD-IPF x longitudinal section; (c) the corresponding statistical grain size distribution; (d) the bright field TEM micrograph along the FCC

[110] zone axis and the inserted selected area electron diffraction pattern show the fully recrystallized grain boundaries and the FCC crystal structure; (e) the g=(220) WBDF image of the representative dissociated dislocations and (f) the Shockley partial separation distance (dact) as a function of the dislocation characteristic angle (β) between the dislocation line and the Burgers vector of the dislocation in the 2% tensile strain sample.

[0070] Figure 7(a) Engineering stress-strain curves of Al2.5Ti2.5(CoCrFeNi)95 HEA wires with different tensile strains and a duration of 1; (b) Relationship between the tensile strength of strain-stabilized fcc alloys and cold drawing strain; (c) Comparison of the engineering tensile strength and elastic modulus of existing alloys and fcc single-phase alloys reported in the literature, ED (electrochemical deposition); SPD (severe plastic deformation) mainly includes CR (cold rolling), SMGT (surface mechanical grinding treatment), ECAP (equal-channel angular pressing), and HPT (high-pressure torsion). HEA wire microstructure: (d1-f1) are EBSD maps, IPF is colored along the wire-drawing direction, (g1) is a TKD map, (g2) is a representative STEM-BF micrograph, and (d2-g2) are STEM-BF micrographs and corresponding SAED patterns, (d1-d2)=0.5, (e1-e2)=1.0, (f1-f2)=3.0, (g1-g2)=5.0.

[0071] Figure 8 BF-STEM micrographs show the microstructure of cold-drawn HEA wires when (a) and (d)=6.0, (b) and (e)=7.0, (c) and (f)=8.0, (a), (b), and (c) are taken from the longitudinal section, and (e), (f), and (d) are taken from the cross-section. (g) and (h) are the aspect ratio and grain size distribution of different strains, respectively.

[0072] Figure 9 Properties of HEA wires (=8.0): (a) Typical bright-field TEM image obtained from the longitudinal section; (b) Atomic distribution maps of Co, Cr, Fe, Ni, Al, and Ti reconstructed by three-dimensional atom probe tomography, revealing the uniformity of atomic distribution; (c) High-magnification bright-field TEM image of the white box area in (a) showing a typical structure; (d) Corresponding SAED pattern within the green dashed box; (e) TKD image corresponding to the area in (c) showing the grain structure and orientation deviation; (f) Point-to-point orientation error measurement along four typical regions in (e); (g) High-magnification TEM image showing nano-twin bundles in the nano-grain region (NGR), and the figure shows NBD (nano-beam diffraction) along the

[110] zone axis; (h) HRTEM image of nano-scale deformation twins, showing many sfs in the twin structure with an FFT pattern (inset). (i) Euler diagram showing pairs of separated grains with an orientation deviation of less than 10°.

[0073] Figure 10 (a) High-energy X-ray diffraction patterns of Al2.5Ti2.5(CoCrFeNi)95 HEA wires annealed after drawing at different strains; (b) Variation of dislocation density with tensile strain; (c) Calculated strengthening contributions and experimental ultimate tensile strengths of wires drawn at different strains (5.5, 6.5, 7.0, 8.0).

[0074] The present invention uses specific examples to illustrate the principle and implementation manner of the present invention. The description of the above embodiments is only used to help understand the method and its core idea of the present invention; at the same time, for those of ordinary skill in the art, according to the idea of the present invention, there will be changes in the specific implementation manner and application scope. In summary, the content of this specification should not be construed as a limitation to the present invention.

Claims

1. A method for preparing a high-strength nanostructured high-entropy alloy wire, characterized in that, Including the following steps: S1. Construct a high-entropy alloy system as the initial alloy. In the high-entropy alloy system, the composition series is designed as Alx(CoCrFeNi)100_x by atomic ratio, where x is 0.1 - 2.5 at.%. S2. Prepare an ingot by vacuum melting the initial alloy, and perform homogenization treatment followed by water quenching. S3. Perform hot forging and machining on the ingot to obtain a bar with a diameter of 5.5 mm. S4. Anneal the bar and then perform water quenching to form a single-phase face-centered cubic structure. S5. Perform multi-pass cold drawing deformation on the annealed bar at room temperature or low temperature to obtain a high-strength nanostructured high-entropy alloy wire composed of a nanocrystalline region embedded with nanotwins and a long fiber crystal region wrapped by high-density dislocations.

2. The method for preparing a high-strength nanostructured high-entropy alloy wire according to claim 1, wherein In step S1, the stacking fault energy is regulated by the addition amount of Al element to promote the formation and evolution of deformation twins and inhibit grain coarsening.

3. The method for preparing a high-strength nanostructured high-entropy alloy wire according to claim 1, characterized in that, In step S1, one or more of Ti, Mo, V, Cu, Mn, Zr, Nb, Si, and B are also included in the high-entropy alloy system.

4. The method for preparing a high-strength nanostructured high-entropy alloy wire according to claim 1, wherein In step S2, the temperature of the vacuum melting is 1873 - 1973 K, and the time is 1 - 2 h.

5. The method for preparing a high-strength nanostructured high-entropy alloy wire according to claim 1, characterized in that, In step S2, the temperature of the homogenization treatment is 1450 - 1500 K, and the time is 5 - 8 h.

6. The method for preparing a high-strength nanostructured high-entropy alloy wire according to claim 1, characterized in that, In step S3, the temperature of the hot forging is 1300 - 1350 K.

7. The method for preparing a high-strength nanostructured high-entropy alloy wire according to claim 1, characterized in that, In step S4, the temperature of the annealing is 1150 - 1200 K, and the time is 1 - 2 h.

8. The method for preparing a high-strength nanostructured high-entropy alloy wire according to claim 1, wherein In step S5, the temperature of the low-temperature environment is 77 K, and the low-temperature environment is a liquid nitrogen environment, which is used to stimulate the cooperative evolution of deformation twins and high-density dislocations and accelerate tissue refinement.

9. The method for preparing a high-strength nanostructured high-entropy alloy wire according to claim 1, characterized in that, In step S5, the cold drawing is carried out to a strain of 8.0 at room temperature and to a strain of 2.0 at low temperature.

10. The method for preparing a high-strength nanostructured high-entropy alloy wire according to claim 1, characterized in that, In step S5, the average grain size of the high-strength nanostructured high-entropy alloy wire is 33 ± 5 nm, the twin thickness is 3 - 4 nm, and the dislocation density is (2.0 ± 0.2) × 10 15 m -2 .